1987
DOI: 10.5271/sjweh.2050
|View full text |Cite
|
Sign up to set email alerts
|

Sensorineural stages of the hand-arm vibration syndrome.

Abstract: stagesof the hand-arm vibration syndrome. Scand J Work Environ Health I3 (1987) [279][280][281][282][283]. Recent work has shown that the vascular signs and neurological symptoms commonly associated with exposure of the hand to vibration may develop independently. A classification for the neurologicalcomponent of the hand-arm vibration syndrome has been developed for those symptoms dominated by sensory afferent involvement, based on the results of objective tests on 634 hands. The first symptomatic stage (lS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(77 citation statements)
references
References 13 publications
1
76
0
Order By: Relevance
“…With current practice, the disability of an employee is only roughly reflected in the widely used methods of staging the hand-arm vibration syndrome (the Stockholm vascular scale and the Stockholm sensorineural stage [1,3]), and other methods may be appropriate [8]. If it were concluded that suitable precautionary measures (especially health surveillance) could have restricted the disease to a lower stage on an appropriate scale, the apportionment of responsibility would be based on the difference between a compensation award appropriate to the higher stage (as experienced by the employee) and an award appropriate to the lower stage (to which the disease should have been restricted).…”
Section: Methods A: Negligence Based On Severity Of Diseasementioning
confidence: 99%
“…With current practice, the disability of an employee is only roughly reflected in the widely used methods of staging the hand-arm vibration syndrome (the Stockholm vascular scale and the Stockholm sensorineural stage [1,3]), and other methods may be appropriate [8]. If it were concluded that suitable precautionary measures (especially health surveillance) could have restricted the disease to a lower stage on an appropriate scale, the apportionment of responsibility would be based on the difference between a compensation award appropriate to the higher stage (as experienced by the employee) and an award appropriate to the lower stage (to which the disease should have been restricted).…”
Section: Methods A: Negligence Based On Severity Of Diseasementioning
confidence: 99%
“…In Japan, a stage classification for peripheral vascular disorders and peripheral nervous disorders was proposed [11]. In 1987, a separation of the vascular and neurological effects in the system of Taylor et al was proposed in the classification of vibration-induced white finger according to the 'Stockholm vascular staging system' [4] and the classification of the neurological effects of handtransmitted vibration according to the 'Stockholm sensorineural staging system' [2].…”
Section: Staging Systemsmentioning
confidence: 99%
“…There are various neurological disorders but, because they not clearly classified, their extent and form are poorly reported and poorly understood. Like vibration-induced white finger, there are staging systems for categorising so-called sensorineural disorders caused by hand-transmitted vibration (e.g., [2]). …”
Section: Introductionmentioning
confidence: 99%
“…The syndrome includes sensorineural, vasospastic, and neuromuscular symptoms, and the disease seems to have a progressive course with continued long-term use of vibrating tools (1,2). After vibration-exposure has ceased, symptoms may be reversed, persist, or even progress (3,4).…”
mentioning
confidence: 99%